Peran Pesantren dalam Membentuk Karakter Santri - Syadidul Kahar; Muhammad Irsan Barus; Candra Wijaya (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2019)
The purpose of this study was to find out the role of the Darusaa'dah Islamic Boarding School in the Pangkalan Susu District of Langkat in the Form of Santri Character The approach used is case study. The object of this research is religious Islamic education institutions. Data sources are people who are directly and indirectly involved with pesantren. To collect these data, the author uses several techniques in data collection, namely documentation, observation and interviews. Data analysis in research uses interpretive patterns that aim to achieve a correct understanding of facts, data and symptoms. In this study researchers focused on two curricula, namely the pesantren curriculum and the general education curriculum. used in the Darusa'dah Islamic Boarding School which is related to character formation. The Darusaa'dah Islamic Boarding School curriculum accommodates students who focus on learning two curricula, namely the pesantren curriculum and the general education curriculum. The pesantren curriculum material taught is sourced from the yellow book which includes; religious laws, monotheism, morals and Arabic. The education curriculum of the Darusaa'dah Islamic Boarding School is focused on the teaching of the Koran, hadith and the books written by the previous ulama. Educational material is presented based on class. The pesantren curriculum and general education curriculum are taught in the Darusaa'dah Islamic Boarding School, as well as forming the character of the santri.